Ketidakpastian Lingkungan, Sistem Akuntansi Manajemen dan Kinerja Manajerial: Dampak Pandemi Covid-19 Pada UKM Batik Solo - Astutik, Erni Puji (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
This study aims to determine the effect of environmental uncertainty on managerial performance mediated by management accounting system during the Covid-19 pandemic. This study takes SMEsÂ  of batik business in Solo as an object, using sample of 107 manager. The sampling technique using purposive sampling. Hypothesis testing using path analysis and Sobel test. The results showed that environmental uncertainty has a significant positive effect on management accounting system and managerial performance, management accounting system has a significant positive effect on managerial performance, and management accounting systems mediates the effect of environmental uncertainty on managerial performance.